General Principles for Credit Reporting - World Bank (Washington, DC, 2013)
Financial infrastructure broadly defined comprises the underlying foundation for a country's financial system. It includes all institutions, information, technologies, rules and standards that enable financial intermediation. Poor financial infrastructure in many developing countries poses a considerable constraint upon financial institutions to expand their offering of financial services to underserved segments of the population and the economy. It also creates risks which can threaten the stability of the financial system as a whole. This report describes the nature of credit reporting elements which are crucial for understanding credit reporting and to ensuring that credit reporting systems are safe, efficient and reliable. It intends to provide an international agreed framework in the form of international standards for credit reporting systems' policy and oversight. The Principles for credit reporting are deliberately expressed in a general way to ensure that they can be useful in all countries and that they will be durable. These principles are not intended for use as a blueprint for the design or operation of any specific system, but rather suggest the key characteristics that should be satisfied by different systems and the infrastructure used to support them to achieve a stated common purpose, namely expanded access and coverage, fair conditions, and safe and efficient service for borrowers and lenders. Section two provides a brief overview of the market for credit information sharing and credit reporting activities and then analyzes in some detail the key considerations underlying credit reporting. Section three outlines the general principles and related roles. Section four proposes a framework for the effective oversight of credit reporting systems.